Extracts of Tectona grandis and Vernonia amygdalina have anti-Toxoplasma and pro-inflammatory properties in vitro - Dégbé Mlatovi; Debierre-Grockiego Françoise; Tété-Bénissan Amivi; Débare Héloïse; Aklikokou Kodjo; Dimier-Poisson Isabelle; Gbeassor Messanvi (Parasite, 2018)
Tectona grandis (teak) and Vernonia amygdalina (bitter leaf) are plants used in traditional medicine in West Africa. In this study, we tested ethanolic and hydro-ethanolic extracts of bark and leaves of T. grandis and ethanolic extract of leaves of V. amygdalina for their inhibitory effect on Toxoplasma gondii, a protozoan parasite responsible for toxoplasmosis. Ethanolic extract of V. amygdalina leaves had proportional contents of phenols, tannins, flavonoids, and polysaccharides. This extract presented the highest efficacy against T. gondii, the lowest cytotoxicity to mammalian cells, but moderate anti-oxidant activity compared to other plant extracts. Ethanolic extract of T. grandis bark also had elevated anti-T. gondii activity, low cytotoxicity on mammalian cells, and one of the highest anti-oxidant activities. However, the phytochemical content of this extract was not very different from the hydro-ethanolic extract, which had no anti-T. gondii activity. In addition, ethanolic extract of V. amygdalina leaves, but not of T. grandis bark, significantly increased the production of TNF-α and NO by antigen-presenting cells. Both extracts had the tendency to decrease expression of major histocompatibility complex molecules at the surface of antigen-presenting cells, while they did not modulate the percentage of apoptotic cells. A study of signalling pathways would help to determine the mechanisms of action of these plant extracts.